English in topics for first - second year students - Baran Adalbert; Барань Адальберт; Bárány Béla (PoliPrint, 2006)
Abstract. English in topics for first - second year students. This material is written to help students.
Англійська мова в тематичних текстах (для студентів I-II курсів неангломовних спеціальностей)
https://opac3.brff.monguz.hu:443/hu/record/-/record/110769
Keywords: English; first year students; second year students